Paraneoplastic encephalitis with leukoencephalopathy in primary fallopian tube carcinoma - Shinagawa, Austin (Radiol Case Rep, 2020)
Previous reports of paraneoplastic encephalitis occurring in primary fallopian tube carcinoma have been exclusively classified as paraneoplastic cerebellar degeneration, with MR imaging either unremarkable or demonstrating cerebellar atrophy. We report a case of paraneoplastic encephalitis in a 64-year-old female with primary fallopian tube carcinoma, reminiscent of N-methyl d-aspartate receptor encephalitis, with MR imaging demonstrating bilateral subcortical and deep white matter T2-FLAIR hyperintensities sparing cerebellar and brainstem structures. To our knowledge, this represents the first reported case of noncerebellar paraneoplastic encephalitis related to primary fallopian tube carcinoma.